Health Promotion in Preschool Children - Yiğit Şenol; Fatma Betül Şenol (MDPI AG, 2023)
The key for individuals to live in health and well-being is the development of healthy living habits. In order for a healthy life habit to be formed, the relevant behaviors must be acquired in the preschool period. This study aimed to promote health knowledge among children attending preschool through health education. The study was designed using the qualitative case study design. The Personal Information Form and Health Hunter Children Follow Health Interview Form were used as data collection tools in the study. Health education activities were implemented in order to improve children's knowledge about health. Activities consisted of physical activity, personal hygiene, injury prevention, sleeping habits, healthy nutrition, healthy life, and paramedic and treatment services categories. Activities were applied to children twice a week for eight weeks. As a result of the study, an improvement was observed in children's knowledge about health. The answers given by the children before and after the Health Education Activities were collected in the categories of nutrition, safe life, illness status, well-being, hygiene, environmental health, and sports.